Co-precipitation synthesis and characterization of NiO-Ce0.8Sm0.2O1.9 nanocomposite powders: effect of precipitation agents - Ding, Changsheng; Lin, Hongfei; Sato, Kazuhisa; Hashida, Toshiyuki (Journal of nanoscience and nanotechnology, 2011)
NiO-Ce0.8Sm0.2O1.9 (NiO-SDC) nanocomposite powders applied as promising anode material for low-temperature solid oxide fuel cells (SOFCs) were synthesized by hydroxide co-precipitation method using NH3 x H2O, NaOH and NH3 x H2O + NaOH as precipitation agents. The crystal phases, morphologies and sintering behavior of the synthesized NiO-SDC nanocomposite powders were investigated by means of X-ray diffraction (XRD), transmission electron microscopy (TEM) and sintering experiments. The effect of precipitation agents on the synthesis of the NiO-SDC nanocomposite powders was discussed. Results show that different precipitation agents influence greatly the synthesis and characteristics of the NiO-SDC nanocomposite powders. The NiO-SDC nanocomposite powders synthesized with NH3 x H2O deviate from the original composition due to the loss of Ni. The loss of Ni is avoided and nano-sized NiO-SDC composite powders are synthesized, when NaOH and NH3 x H2O + NaOH are used as precipitation agents. The NiO-SDC nanocomposite powders can be synthesized at relatively low temperature using NH3 x H2O + NaOH as precipitation agent, and the synthesized NiO-SDC nanocomposite powders show good sintering characteristics.